2021
DOI: 10.12688/hrbopenres.13416.1
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and functional alterations in the oral and gut microbiota in patients with psychosis or schizophrenia: A systematic review

Abstract: Background: Gut and oral microbiota are intrinsically linked to human health. Recent studies suggest a direct link with mental health through bidirectional gut–brain pathways. Emerging evidence suggests that the composition and/or function of intestinal microbiome differs in those with psychosis and schizophrenia as compared with controls. There is relatively little research on the predicted or actual functional alterations associated with the composition of oral and gut microbiota in patients with psychosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Furthermore, the ROC curve analysis showed that alpha diversity was able to diagnose AD, schizophrenia, and MS. These results demonstrate dysregulation and alteration in gut microbiota in AD, schizophrenia, and MS, which had been confirmed in the previous studies (Murray et al, 2021 ; Cantoni et al, 2022 ). Dysregulation of gut microbiota could facilitate the occurrence and development of neurological diseases, in which the “gut microbiota-brain” axis might play an important role (Almeida et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the ROC curve analysis showed that alpha diversity was able to diagnose AD, schizophrenia, and MS. These results demonstrate dysregulation and alteration in gut microbiota in AD, schizophrenia, and MS, which had been confirmed in the previous studies (Murray et al, 2021 ; Cantoni et al, 2022 ). Dysregulation of gut microbiota could facilitate the occurrence and development of neurological diseases, in which the “gut microbiota-brain” axis might play an important role (Almeida et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…The authors added that it could be explain by a decrease immune surveillance in the gut. This point gives us another hypothesis for the OBA: the link between oral microbiome and schizophrenia could be made throughout the gut microbiota [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…They added that this pointing to the relation between oral resident bacteria and gut bacteria, suggesting that oral resident bacteria in a synergistic manner may colonize the gut in schizophrenic patients. A study is currently underway to clarify the relationship between the composition of the oral and intestinal microbiota in patients with psychosis or schizophrenia and healthy controls [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these patients may also display an increased intestinal permeability [ 38 ]. To date, nearly a dozen studies have reported differences in the microbiome between healthy individuals and patients at different stages of the disease [ 39 , 40 ]. Nevertheless, their results are not consistent, especially when analyzing bacterial components in a higher taxonomic order.…”
Section: Discussionmentioning
confidence: 99%